2005
DOI: 10.1093/gerona/60.10.1351
|View full text |Cite
|
Sign up to set email alerts
|

Health Changes Among Swedish Oldest Old: Prevalence Rates From 1992 and 2002 Show Increasing Health Problems

Abstract: In light of several recent studies, we expected to observe improvements in the health of the elderly population. However, this study showed no signs of improvement. On the contrary, we found a pattern of worsening health. The study included objective tests of function, implying that results are not due solely to raised expectations or changes in reporting. Possible explanations are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
110
2
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 21 publications
10
110
2
3
Order By: Relevance
“…Previous analyses of SWEOLD data, however, found no significant differences in ADL limitations between 1992 and 2002 (Parker et al 2005). It is important to understand that health problems do not always lead to disability and limitations in ADL's.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous analyses of SWEOLD data, however, found no significant differences in ADL limitations between 1992 and 2002 (Parker et al 2005). It is important to understand that health problems do not always lead to disability and limitations in ADL's.…”
Section: Discussionmentioning
confidence: 93%
“…A study carried out with the same SWEOLD data confirmed the significant worsening of health between 1992 and 2002 when examining tests of function (peak flow, physical performance, cognition). Tests are less vulnerable to reporting differences, rising expectations and environmental modifications (Parker et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the picture is less clear concerning the late 1990s. There are other studies from Sweden (Parker et al 2005) pointing out that health status among the older adults may have been deteriorating in the beginning of 2000. The available evidence does not unambiguously imply that one of our scenarios is more likely to occur than the others.…”
Section: Discussionmentioning
confidence: 99%